The Cyrillic between religion and politics - Prodić, Slobodan (Napredak, 2023)
One of the attributes of the Cyrillic is that it has been exposed to numerous attacks in the aim of particular or total extinction since its creation. Those who are against Christianity are also against the Cyrillic, as the Cyrillic was created because of the expanding Orthodox religion among Slavs. The fight against the Church includes the fight against the Cyrillic. There have been different types of these fights, but they have often had a political background. Therefore, we can say that for centuries the Cyrillic has been the target of different oppressors who tried and are still trying in different ways to destroy the Orthodox-Christian identity of both Serbian and other nations whose existence and survival also depend on their script and language.